Modelo de comercialización de leche para la Asociación de Ganaderos del cantón Tosagua - Alcívar Cedeño, Javier Atilio (2011)
This work is primarily to establish a marketing model that allows milk producers to facilitate a better trade and optima) use of existing production areas on the site Tambo, Canton Tosagua. For the development of this research was used as tools survey, statistical graphs, that allowed to diagnose the reality of trade, which sets the preferentes in choosing the available product to consume milk that evokes freshness quality and purity as well as different types of layouts available in the market. For this reason a marketing modal was developed for the milk Cattlemen's Association in Tosagua Canton, the same which includes corporate and marketing strategies, determinants for the formation of an optimum milk trade and the respective economic and financial analysis that shows the viability of this proposal. In conducting the financial study, the intemal rafe of return and net present value shows the project as viable. The interna) rate of return on investment is 38% while the net present value is 162,972.19, with these strategies is evident the benefits of the marketing and financially, which constitutes a fundamental altemative not only to boost socially and financially the Canton's economy but also the technical development of the production processes and marketing.